PERBANDINGAN TINGKAT KEBUGARAN JASMANI SISWA KELAS X BERDASARKAN LETAK GEOGRAFIS (STUDI PADA SISWA PUTERA KELAS X SMA NEGERI 1 NGADIROJO DAN SISWA PUTERA KELAS X SMA NEGERI 1 TULAKAN) - HARIYONO, RINO (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical fitness is one’s ability to do daily activities without arousing any significant fatigue, so that the body still has reserve power to solve the extra activities. Therefore, children need a lot of attention from their parents, especially about their physical fitness level so their growth can run optimally. Since physical fitness is very important for life, we should be able to develop childhood physical fitness program. The purpose of this research is to know the comparison of male students’ physical fitness level in the tenth grade of SMA Negeri 1 Ngadirojo who go to the school in the lowland area with male students in the tenth grade of X SMA Negeri 1 Tulakan who go to school in the highland area. Research method used is non-experimental research with descriptive qualitative approach. The population is male students in the tenth grade of SMA Negeri 1 Ngadirojo and SMA Negeri 1 Tulakan. The sampling in this research for all are 46 students. The result can be concluded that: 1) There are a significant differences, with level of significance 0,05 between male students’ physical fitness level in the tenth grade who go to school in the lowland area and who go to school in the highland area. These differences can be seen on the result of MFT test for male students who go to school in the lowland area have average score as 36,043; standard deviation as 4,9012; and variant score as 24,023. While the result of MFT test for male students who go to school in the highland area have average score as 42,143; standard deviation as 6,03; and variant score as 36,3616. Therefore, the result of Independent sample t-test is tcount (3,76) > ttable (2,021). In other words, we can say that there are significant differences between male students’ physical fitness level in the tenth grade who go to school in the lowland area and who go to school in the highland area. 2) From the result of t-test, students who go to school in the highland area are better than students who go to school in the lowland area with percentage as 8,54%. 3) From that data, students of SMA Negeri 1 Tulakan which belongs to highland area have bigger physical fitness than students of SMA Negeri 1 Ngadirojo which belongs to lowland area. Keywords: Physical Fitness Level, Lowland Area, Highland Area